A fluoropolymer with a low dielectric constant at a high frequency derived from bio-based anethole. Issue 31 (21st July 2021) - Li, Minghui; Sun, Jing; Fang, Qiang
Abstract : The copolymerization between a fluoro-containing monomer derived from bio-based anethole and a benzocyclobutene (BCB)-containing monomer gave a polymer with good dielectric properties and low water uptake. Abstract : A new fluoro-containing monomer (M1 ) with a high fluoro content derived from anethole was synthesized, which was copolymerized with a monomer (M2 ) having benzocyclobutene units to give a resin, showing a dielectric constant ( D k ) of 2.50 and a dielectric loss ( D f ) of 1.4 × 10 −3 at a high frequency of 5 GHz. This resin also exhibited a 5% weight loss temperature of up to 460 °C and a water uptake of 0.14%. These data indicate that this bio-based fluoro-containing monomer is suitable as an encapsulation material for application in microelectric fields. The cured resins with different molar ratios of M1 to M2 show that the resin with a molar ratio of 1 to 1 exhibits the best dielectric properties. With the increase of M2, the cured resins show higher heat resistance.